2011
DOI: 10.3319/tao.2011.05.12.01(tm)
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Track and Structure Sensitivity to Initialization in Idealized Simulations: A Preliminary Study

Abstract: In the absence of environmental steering, tropical cyclone (TC) motion largely reflects "beta drift" owing to differential planetary vorticity advection by the storm's outer circulation. It is known that model physics choices (especially those relating to convection) can significantly alter these outer winds and thus the storm track. Here, semi-idealized simulations are used to explore the influence of the initialization on subsequent vortex evolution and motion. Specifically, TCs bred from a buoyant "bubble" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
0
19
1
Order By: Relevance
“…5), regardless of the prescribed R34 value, which has no significant impact on the intensity forecast. The results obtained here for a real TC case differ from the semi-idealized simulations of Cao et al (2011). 9) where SM18, the rightmost point, appears as an outlier to the trend.…”
Section: A Impact Of Vortex Initialization On the Intensity Forecastcontrasting
confidence: 86%
See 2 more Smart Citations
“…5), regardless of the prescribed R34 value, which has no significant impact on the intensity forecast. The results obtained here for a real TC case differ from the semi-idealized simulations of Cao et al (2011). 9) where SM18, the rightmost point, appears as an outlier to the trend.…”
Section: A Impact Of Vortex Initialization On the Intensity Forecastcontrasting
confidence: 86%
“…As the storm slows down, b propagation becomes gradually significant under weak environmental influences. Such lack of sensitivity to the R34 differs from Cao et al (2011) and suggests a possible case dependency for storms with strong outer wind structures in weak environmental flows. It acts more efficiently when the initial wind distribution is specified with sufficient strength and extent especially at outer radii (larger initial RMW), consistent with Chan and Williams (1987).…”
Section: B Importance Of Initial Storm Structure On B Propagationmentioning
confidence: 90%
See 1 more Smart Citation
“…where r is the radial distance, and X is the scaling parameter that adjusts the velocity distribution in the radial direction [18]. The theoretical value for X is 0.5 [55,56], and typical values in the literature for X in the Atlantic and Pacific TCs are between 1/3 and 2/3 [57]. For example, Mallen et al [58] found mean values for major TC (V max > 50 m/s) of 0.48 and progressively smaller values for the less intense TCs.…”
Section: Parametric Wind Fieldsmentioning
confidence: 99%
“…ocean model, employing a uniform and constant sea surface temperature (SST) of 302.5 K for the standard runs, and initializing with a horizontally homogeneous tropical sounding [modified from Jordan (1958); see Fovell et al (2010)] without any mean flow. The Cao et al (2011) ''bubble'' procedure was used to initiate the TC and all simulations spanned 4 full days with composite model fields being constructed for the final day in a vortex-following fashion, averaging over one full diurnal cycle. While changes in operational settings (primarily with respect to horizontal smoothing) from the 2013 version used by Bu et al (2014) resulted in somewhat weaker storms for the same experimental design, all of the standard SST HWRF TCs attained major hurricane status (at least category 3 on the Saffir-Simpson scale) for the analysis period.…”
Section: Model and Experimental Designmentioning
confidence: 99%